A marcoprolactinemia: da determinação laboratorial ao seu significado clínico - Matos, C (2011)
Since prolactin (PRL) (a hormone produced by the anterior pituitary) was first identificated, the existence of hyperprolactinemic syndrome has been recognized. Main symptoms are galactorrhea, oligomenorrhea, amenorrhea and infertility in women and decreased libido and impotence in men. Macroprolactinemia reflects the predominance of circulating forms with reduced bioactivity not associated with typical clinical manifestations of hyperprolactinemia. It is identified by immunoassays commonly used in clinical practice, resulting in hyperprolactinemia. Polyetilenoglycol (PEG) is the most used method that removes PRL from serum. It is likely that the phenomenon of macroprolactinemia is consistently underestimated and unrecognized. Manufacturers of immunoassays for PRL have been slow to incorporate in the literature, validated protocols, and data related to the interference of PEG. From a clinical and biochemical point of view and, the main concern should be to avoid unnecessary investigation and treatment.